Entropy of interval maps via permutations - Brandt, Christoph; Keller, Gerhard; Pompe, Bernd (Nonlinearity, 2002)
For piecewise monotone interval maps, we show that the Kolmogorov-Sinai entropy can be obtained from order statistics of the values in a generic orbit. A similar statement holds for topological entropy.
UnivIS-Import:2015-03-09:Pub.2002.nat.dma.pma29.entrop